Vitiligo in equine: a four-year case study of a roan horse - case report [Vitiligo em equinos: um estudo de caso de quatro anos de um cavalo roan - relato de caso] - Valente T.C.* (2021)
© 2021. All Rights Reserved.Vitiligo is a dermatological disease affecting both animals and humans. It is characterized by depigmented macules of varying shape and size, originated from melanocyte destruction. Even though there are some theories tackling causation, disease etiopathology is not yet certain. Moreover, lesion areas can either increase or diminish over time, and therefore, available treatment alternatives tend to prove inconsistencies. No epidemiological data or registered cases were found for equines in Brazil. The horse in this case description displayed depigmentation areas in facial regions, including upper lip, nose and lips. However, the individual did not happen to develop any systemic alteration. Through clinical evaluation, backed by a histopathological exam, a definitive vitiligo diagnosis was obtained. However, no therapeutic plan was stipulated. The animal was accompanied for four years, during which period some affected areas diminished while others increased in size. In addition, emergence of new skin lesions was also observed during the time the animal was studied. Overall, this disease does not display alterations to organism functionality, only aesthetic changes. Therefore, treatment plans may vary from case to case, occasionally being even ruled out.